Wolf worm - Kingfisher, T. (Nightfire, Tor Publishing Group, 2026)
"Sonia Wilson is a talented scientific illustrator--but she is only able to follow her dream because of her father's reputation as a renowned scientist. Such is the lot in life for a woman in science in 1899. And after his death, she is left without work, prospects, or hope. So when the reclusive Dr. Halder offers her a position illustrating his vast collection of insects, Sonia jumps at the chance to move to his North Carolina manor house and put her talents to use. Once there though, she encounters dark happenings in the Carolina woods, and even darker questions come to light, like what happened to her predecessor? Why are animals acting so strangely, and what is behind the peculiar local whispers about 'blood thiefs?' With the aid of the housekeeper and a local healer, Sonia discovers that Halder's entomological studies have taken him down a twisted road. His ground-breaking discoveries come with a cost--one that Halder is paying with human flesh. If Sonia can't find a way to stop the monstrosity, she may be next under the knife." --